Maize Biodiversity and Food Security Status of Rural Households in the Derived Guinea Savannah of Oyo State, Nigeria (2016)
The incidences of food insecurity and loss of crop biodiversity are devastating in the developing countries including Nigeria. Th e continued loss of genetic diversity of agricultural crops has major negative consequences on food security. Th is study examined the eff ects of maize biodiversity on household food security status of rural maize farm households in the southern guinea savannah of Oyo State, Nigeria. A multistage sampling procedure was used to select 200 maize-farm households. Th e data were analysed using descriptive statistics, recommended daily calorie approach, Logit model, agro-biodiversity indices (Margalef, Shannon and Simpson) and the two-stage least Square. Based on the Food and Agriculture Organization (FAO) recommended daily energy requirement of 2260 Kcal, about 76.5% of the rural households were food secure. Th e highest proportion of the farmers with abundance of maize cultivars were within 30 to 49 years old, with fi ve to nine household members, had formal education and 10-19 years of farming experience and cultivated fi ve to nine hectares of farmland. Food security headcount increases with maize richness, cultivar evenness and relative abundance. Most of the farmers grow improved varieties such as ‘Tsolo’, ‘NS-1’, ‘N.S 5’, ‘TZB’, ‘TZBP’, ‘OBA Supper’ (Yellow and White) and Popcorn varieties. Farmers growing Tsolo had the highest percentage of abundance, while the least abundant species were ‘NS-1’, ‘N.S 5’, ‘TZB’, ‘TZBP’, ‘OBA Supper’ (Yellow and White) and Popcorn varieties. Disaggregation of maize diversity into its components showed that its eff ect on household food security status was based on the age of the farmer and the annual gross farm income. Maize diversity is positively related and truly endogenous to household food security status without reverse causality.